The Building of Mathematical Concepts When Solving Mathematical Tasks in Traditional Way and Using Graphing Calculators - Martins, Helder Manuel; Domingos, António Manuel (Pedagogika, 2025)
This article aims to understand how students learn mathematical concepts related to the study of functions and differential calculus using graphing calculators with the computer algebra system (GCC) and traditional methods. With a qualitative methodology, we show that students can make the transition to mathematical meanings of concepts using both processes.